농촌 보건의료 서비스체계 개선방안 - 최경환 (한국농촌경제연구원, 2008)
Health care service in Korea is provided based on the laissez-faire principle, and the private sector accounts for as much as 90% of the domestic health care market. Furthermore, most health care facilities are located in urban areas, whereas they are scarce in rural areas. And yet, it is difficult to expect much improvement in health care service in rural areas in the foreseeable future. The government has been trying to improve the rural health care environment to provide better health care services to rural residents including farmers. The main projects that have been pursued by the government so far are establishment of Health Centers since the early 1960s, introduction of Public Health Doctors since the early 1980s, and execution of Rural Health Care Service Improvement Project since the mid-1990s. These policies have resulted in no areas without a doctor in rural areas, facilitating every rural village with basic health care facilities and raising rural residents' accessibility to health care services through Public Health Centers, Sub-Public Health Centers, and Primary Health Care Posts. In short, the hardware for rural health care is relatively enovgh while the software is lacking. The circumstances for rural health care service are changing rapidly alongside economic development and advancement in medicine, transportation and IT industry. The ever increasing chronic diseases stemming from modern lifestyles and rural residents' heightened interest in health have also contributed to this change. Moreover, the number of Public Health Doctors is expected to drop drastically due to reduced student enrollment ceiling for medical colleges and introduction of a new education system for postgraduate medical studies. In consideration of these changing circumstances, this paper suggests that an Attending Physician System be introduced in rural areas to improve rural health care service fundamentally, and it will be helpful to test a pilot program before nationwide execution. As differences among rural areas are very large with respect to population, ratio of the elderly, transportation infrastructure and so on, each region's characteristics need to be considered in redesigning the Regional Health Care Plan every four years. Researcher: Choi Kyeong-Hwan Research period: 2008.1～2008.7 E-mail Address: kyeong@krei.re.kr